2021
DOI: 10.21203/rs.3.rs-1158065/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Ambient Lighting on Frequency Dependence in Transcranial Electrical Stimulation-Induced Phosphenes

Abstract: Inconsistencies have been found in the relationship between ambient lighting conditions and frequency-dependence in transcranial electric current stimulation (tECS) induced phosphenes. Using a within-subjects design across lighting condition (dark, mesopic [dim], photopic [bright]) and tECS stimulation frequency (10, 13, 16, 18, 20 Hz), this study determined phosphene detection thresholds in 24 subjects receiving tECS using an FPz-Cz montage. Minima phosphene thresholds were found at 16 Hz in mesopic, 10 Hz in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A lingering question is whether neural input from the occipital cortex alone produces a phosphene response. Transcranial alternating current stimulation (tACS) experiments with currents applied into various sites, including the occipital cortex 20,22,26,33,34 , have documented phosphene responses, with some suggestions 20,22,26 (but not concrete evidence) of a direct effect. Laakso and Hirata demonstrated that tACS current from the scalp through the retina can exceed the phosphene threshold 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A lingering question is whether neural input from the occipital cortex alone produces a phosphene response. Transcranial alternating current stimulation (tACS) experiments with currents applied into various sites, including the occipital cortex 20,22,26,33,34 , have documented phosphene responses, with some suggestions 20,22,26 (but not concrete evidence) of a direct effect. Laakso and Hirata demonstrated that tACS current from the scalp through the retina can exceed the phosphene threshold 28 .…”
Section: Discussionmentioning
confidence: 99%
“…General psychological training aims to improve the psychological factors of athletes related to special sports and is also called long-term psychological training because it can be arranged throughout the training process. Psychological training in preparation for specific competitions is mainly for the specific competition and psychological preparation, generally in the two or three months before the competition to start practicing, and continues until the competition period pregame special psychological training aims to enable athletes to master and use the method of self-regulation of mental state in a relatively short period of time, in order to form the best competitive state [4][5][6].…”
Section: Introductionmentioning
confidence: 99%